RECENT ADVANCES APPLICATION IN DIFFUSE AXONAL INJURY IMAGING (DAII) AND FUTURE PROSPECTIVE : A COMPARATIVE STUDY WITH SYSTEMATIC REVIEW OF LITERATURE (Journal of Forensic Medicine & Toxicology, 2015)
Background: Diffuse axonal injury (DAI) is the brain injury in which damage in the form of an extensive lesions in white matter tracts occurs over a widespread area. DAI is one of the most common and devastating types of traumatic brain injury (TBI). Material and metods: We reviewed from from different data set like pubmed/medline and google resources were retrospectively we reviewed to identify patients underwent both CT and MRI examinations of the head and patients were found with diagnostic images were available for DAI and de-identified images reported by ealier world literature.Presence of any injury, intracranial hemorrhage, diffuse axonal injury (DAI), and skull fracture also reviewed here in systematically. Results: It occurs in about half of all cases of severe head trauma and outcome is frequently coma, with over 97% of patients with severe DAI never regaining consciousness.Those who do wake up often remain significantly impaired. So DAI can occur in every degree of severity from very mild or moderate to very severe. MRI more frequently reported intracranial findings of CT scanning. No statistically significant difference observed between CT and MRI in the detection of any intracranial injury.
Keywords: Diffuse axonal injury; traumatic brain injury; x-ray; CT; MRI